1974
DOI: 10.1161/01.str.5.6.765
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Observations on the Luminal Surface of the Rabbit Common Carotid Artery Sublected to lschemia by Arterial Occlusion

Abstract: Abstract• The scanning electron microscope (SEM) has been employed to study the effects of ischemia on the luminal surface of the common carotid artery. Fifteen adult rabbits were lightly anesthetized and the common carotid arteries surgically exposed. The right carotid artery was occluded with a single Heifetz clip for five minutes (five animals), 15 minutes (five animals), and 30 minutes (five animals). Following removal of the clip, the animals were immediately perfused with glutaraldehyde and the arteries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 8 publications
(4 reference statements)
0
27
0
Order By: Relevance
“…The craters seem to be ruptured or collapsed balloons, as Kawamura et al 13 have pointed out, because transitional forms of both conditions and the concave surface of craters occasionally revealed plasmalemmal pits and microvilli exactly as seen on the endothelial surface. Nelson et al…”
Section: Discussionmentioning
confidence: 80%
“…The craters seem to be ruptured or collapsed balloons, as Kawamura et al 13 have pointed out, because transitional forms of both conditions and the concave surface of craters occasionally revealed plasmalemmal pits and microvilli exactly as seen on the endothelial surface. Nelson et al…”
Section: Discussionmentioning
confidence: 80%
“…We have shown previously that injury appearing as craters and balloons on SEM represents protruding blebs and vacuoles as seen with transmission electron microscopy.6 ' These alterations have been reported after a wide variety of injurious stimuli as well as "&spontaneously" at branch orifices,8 suggesting that these alterations represent a nonspecific reaction of endothelial cells to injury. 6 We have demonstrated that the carotid or coronary arteries that were subjected to 40-60% reduction in luminal diameter (resulting in no substantial change in the rate of distal blood flow) showed endothelial desquamation and thrombus formation only on the proximal slope ( fig. 1, segment 3), particularly in the area just proximal to the point of maximum constriction figs.…”
Section: Discussionmentioning
confidence: 91%
“…Hoff, 1970;Shimamoto & Numano, 1973;Kawamura et al, 1974;Nelson et al, 1975;Gertz, Rennels & Nelson, 1975). The transmission electron microscope (TEM) has permitted the identification of fine structural changes within endothelial cells and intercellular junctions.…”
Section: Introductionmentioning
confidence: 99%